Histopathologic changes and incidence of gall bladder lesions in consecutive 576 gall bladder surgeries. - metib, nazar (Karbala Journal of Medicine, 2019)
Background : Cholecystectomies with relevant frequency of gall bladder pathologies is not clear. Patients and methods:throughout 2016 and 2017 in pathology unites of two hospitals ,576 cholecystectomy cases were analysed. The age of the patients range from 2 to 80 years with a mean of 42.60 ± 15.62 years. Male to female ratio was 152:424 (1:3).All of the samples examined and reviewed by two consultant pathologists . Aim of study:The aim of this study is to report the pathologic changes and frequency of gall bladder diseases and lesions in 576 cholecystectomies Results and discussion:Of these gall bladder samples ,437 cases (75.9%) had gall stones,51 cases (8.9%) were acute cholecystitis, 464 cases (80.6%) were chronic cholecystitis ,9 were malignant (1.6%) and 52 were normal (9%).All the malignant cases were solid variant adenocarcinomas and only one was metastatic from sigmoid colon.The frequency of histopathologic lesions were acute suppurative 24 cases (4.1%) ,xanthogranulomatous cholecystitis 34 (6.1%),Rokitansky – Aschoff sinuses seen in 223 (38.7%),inspissated bile 24 (4.2%),adenomyomatous changes 146 (25.3%),focal abscess formation 26 (4.5%), cholesterosis 31 (5.4%),metaplasia 465 (80.7%),single adenomatous polyp , eosinophilic cholecystitis 25 (4.3%). In adenomyomatous changes the epithelial proliferation was florid with Rokitansky – Aschoff sinuses and smoth muscle hypertrophy . Metaplastic changes were of pyloric,intestinal and mucous glands types,the adenomatous polyp was of biliary type with low grade epithelial atypia .In the present study there were no heterotopic tissue or intraepithelial neoplasm . Conclusion:The available data may provide basic knowledge of the gall bladder pathologies.